Adaptive optics retinal imaging in patients with retinal disease - Shah, M (2020)
High-resolution in vivo retinal imaging with an adaptive optics scanning laser ophthalmoscope (AOSLO) allows visualisation of degenerative changes at the cellular level. The improvement in resolution with this type of imaging when compared to conventional retinal imaging technologies has made the use of cell-specific imaging biomarkers possible. With the development of new therapies for retinal disease, cell-specific biomarkers of disease are becoming increasingly important for monitoring treatment outcomes. This thesis aims to investigate the AOSLO as a clinical tool and to develop fully automated image processing and analysis pipelines for AOSLO images from patients with retinal disease.